2021
DOI: 10.1126/science.abi8183
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene materials with in-chain ketones from nonalternating catalytic copolymerization

Abstract: Polyethylene with a nickel’s worth of CO The biggest problem with polyethylene, the most abundantly manufactured plastic, is that it doesn’t break down easily once it is discarded. Chemists have long sought to introduce small quantities of carbon monoxide (CO) into polyethylene chains to promote photodegradation, but too much CO tends to jump in and spoil the plastic’s other properties. Baur et al . report that nickel catalysts coordinated by bulky phosphinophenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
173
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(181 citation statements)
references
References 46 publications
4
173
1
3
Order By: Relevance
“…Subsequent reaction with NaH afforded the desired nickel complex ( Ni-ONa ) in near-quantitative yield. Inspired by Mecking and coworkers’ recent works on perfluorophenyl-substituted phosphinophenolate nickel catalyst 11 , the corresponding OH and ONa tagged nickel catalysts ( Ni-F-OH and Ni-F-ONa ) were also prepared. 1 H NMR characterization showed the coexistence of Ni- Me and Ar- OH signals in both Ni-OH and Ni-F-OH , and the integration of Ni- Me signal matched very well with the rest of the ligand signals (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent reaction with NaH afforded the desired nickel complex ( Ni-ONa ) in near-quantitative yield. Inspired by Mecking and coworkers’ recent works on perfluorophenyl-substituted phosphinophenolate nickel catalyst 11 , the corresponding OH and ONa tagged nickel catalysts ( Ni-F-OH and Ni-F-ONa ) were also prepared. 1 H NMR characterization showed the coexistence of Ni- Me and Ar- OH signals in both Ni-OH and Ni-F-OH , and the integration of Ni- Me signal matched very well with the rest of the ligand signals (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Industrially successful early transition-metal catalysts cannot perform such tasks due to the poisoning effects of polar groups towards metal centers. Within this context, late-transition-metal-based olefin polymerization catalysts have received continuous interest because of their low oxophilicity and correspondingly high tolerance towards polar groups 11 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Given that the xenon lamp (covering the wavelength of sunlight) was not as effective as the 275 nm UV light for the copolymer degradation, the material may be decomposed on-demand upon UV irradiation. It should be noted that during our study, new catalysts 4a and 5a were developed by Chen 10 ) and Mecking 11 ) independently, for lowering the content of the alternating structure in the ethylene/CO copolymers. Mecking reported that the mechanical property, the stress–strain curves, of the ketone-containing polyethylene (0.6 mol% of CO) is also similar to that of polyethylene.…”
Section: C1 Comonomersmentioning
confidence: 94%
“…[335] In recent advances, nickel and palladium catalysts were successfully tailored to enable random incorporation of small amounts of carbon monoxide into PE chains. [336,337] High-molar-mass PE containing few isolated in-chain ketone groups is rendered photodegradable without adversely affecting PE-like processing or property profiles. More research is needed to clarify the fate of the resulting photodegraded PE fragments in the environment.…”
Section: Oxo-and Photodegradationmentioning
confidence: 99%